Gambaran Dislipidemia pada Penderita Gagal Ginjal Kronik di Rumah Sakit Dr. Wahidin Sudirohusodo Makassar - Nurlia Ahmad; Nahir Bandu; Dita Ellyana Artha (Jurnal Media Laboran, 2018)
Drugs for chronic renal failure (CRF) in Dr. WahidinSudirohusodo Hospital. The aim of this research is to find out what the total cholesterol is, cholesterol low LDL (Low Density Lipoprotein), cholesterol HDL (High Density Lipoprotein) and triglycerides. Research on 34 samples with cross sectional method, from the date of July 5th 2010 to 7th September 2010.Tests using a chemical autoanalyzer (ABX Pentra 400). The results obtained showed that patients with chronic renal failure who had dyslipidemia as much as 18 patients (53%) of 34 patients. The number of men as many as 10 patients (55%) and female 8 patients (45%).Hypertriglyceride as much as 56% with levels (186 ± 72) mg / dl, HDL as much as 53%, with levels (35 ± 10) mg / dl, Hypercholesterolemia as much as 38% with levels (245 ± 82) mg / dl, LDL as much as 35% with levels (178 ± 82) mg / dl.